Activation of the AIM2 Receptor in Circulating Cells of Post-COVID-19 Patients With Signs of Lung Fibrosis Is Associated With the Release of IL-1α, IFN-α and TGF-β - Colarusso, Chiara; Terlizzi, Michela; Maglio, Angelantonio; Molino, Antonio; Candia, Claudio; Vitale, Carolina; Hansbro, Philip M.; Vatrella, Alessandro; Pinto, Aldo; Sorrentino, Rosalinda (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome-coronavirus-2 (SARS‐CoV‐2), responsible for COVID-19, has caused a global pandemic. Observational studies revealed a condition, herein called as Long-COVID syndrome (PC), that affects both moderately and severely infected patients, reducing quality-of-life. The mechanism/s underlying the onset of fibrotic-like changes in PC are still not well defined. The goal of this study was to understand the involvement of the Absent in melanoma-2 (AIM2) inflammasome in PC-associated lung fibrosis-like changes revealed by chest CT scans. Peripheral blood mononuclear cells (PBMCs) obtained from PC patients who did not develop signs of lung fibrosis were not responsive to AIM2 activation by Poly dA:dT. In sharp contrast, PBMCs from PC patients with signs of lung fibrosis were highly responsive to AIM2 activation, which induced the release of IL-1α, IFN-α and TGF-β. The recognition of Poly dA:dT was not due to the activation of cyclic GMP-AMP (cGAMP) synthase, a stimulator of interferon response (cGAS-STING) pathways, implying a role for AIM2 in PC conditions. The release of IFN-α was caspase-1- and caspase-4-dependent when AIM2 was triggered. Instead, the release of pro-inflammatory IL-1α and pro-fibrogenic TGF-β were inflammasome independent because the inhibition of caspase-1 and caspase-4 did not alter the levels of the two cytokines. Moreover, the responsiveness of AIM2 correlated with higher expression of the receptor in circulating CD14+ cells in PBMCs from patients with signs of lung fibrosis.